Language curriculum design - John Macalister; I. S. P. Nation (New York : Routledge, 2020)
"Now in its second edition, Language Curriculum Design describes the steps involved in the curriculum design process, elaborates and justifies these steps, and provides opportunities for practicing and applying them. Crystal-clear and comprehensive yet concise, the steps are laid out at a general level so that they can be applied in a wide range of particular circumstances. Updated throughout with cutting-edge research and theory, the second edition contains new examples on curriculum design and development and expanded attention on environment analysis, needs analysis, and program evaluation. The process comes to life through plentiful examples of actual applications from the authors' experience and from published research. Each chapter also includes tasks that encourage readers to relate the steps to their own experience, and case studies and suggestions for further reading. Combining sound research/theory with state-of-the-art practice, Language Curriculum Design is widely applicable for ESL/EFL language education courses around the world"-- Provided by publisher
Keywords: English language Study and teaching